Construção e validação da escala de avaliação do autocuidado de pacientes com insuficiência cardíaca - Oliveira, Shérida Karanini Paz de (2011)
It is important to evaluate the practice of self-care of patients with heart failure (HF), as the personal care is essential to decrease complications and readmissions and improve the quality of life. This study aimed to develop a scale for evaluate self-care of patients with heart failure and perform content validation of self-care scale for evaluation of patients with heart failure. It is a methodological study, whose theoretical reference was the Psychometric model for construction of measuring instruments composed of three procedures (theoretical, empirical and analytical), beeing performed the theoretical pole and its six steps . The first stage of the research involved the investigation of the elements that comprise the multiple facets of the construct "self-care of patients with heart failure" through a literature review. For this, we proceeded to search for scientific articles in national journals and international databases and scholarly books about HF and self-care in the university libraries in the months of April and May 2011. We selected 63 articles that met criteria for inclusion in databases SCOPUS, PubMed, CINAHL, Cochrane Library and LILACS after the crossing of controlled descriptors self-care and heart failure and their translations into English and Spanish. Regarding the books, we selected eight books that met the inclusion criteria established. Reading and summaries of articles and books have been identified 28 practice of self-care of patients with HF guided the operationalization of the construction of the scale, resulting in the first version of the Scale of Evaluation of Self-Care of Patients with Heart Failure (EAAPIC). Data collection with the judges took place in August, September and October 2011, we used a form containing data regardings jugdes and evaluate data on the scale. The study complied with the ethical guidelines and was approved by research ethics committee of the Federal University of Ceará under protocol number 114/2011. The first version of the instrument comprised 29 items divided into seven areas, namely: nutrition, elimination, activity and rest, perception and cognition, health promotion, stress tolerance, and roles and relationships. And each item had five possible answers arranged in Likert scale ranging from 1 to 5, with 1 considered worse self- care and 5 the best self-care. There has been the theoretical analysis of the scale, submitting to the evaluation of eight judges considered experts in heart failure. After statistical tests (Index of Validity of Content - IVC and coefficient of intraclass correlation - ICC) and the changes resulting from the suggestions of the judges, we obtained the second version of the scale consisting of twenty items divided in six areas. ICC of EAAPIC was 0.827 (p= 0,001), indicating good internal consistency. We conclude, therefore, that it was possible to construct a evaluation scale of self-care of patients with heart failure and that it involves and represents the content of the construct to be measured due to its good value for coefficient of intraclass correlation.